2013
DOI: 10.1016/j.apnu.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Evaluation of an Interpersonal and Social Rhythm Therapy Group Delivery Model

Abstract: The effectiveness of psychotherapies, such as interpersonal and social rhythm therapy (IPSRT), is supported by randomized controlled trials. These trials provide minimal direction regarding feasibility of psychotherapy delivery models. The study purpose was to identify factors facilitating implementation and sustainability of an IPRST group for patients with bipolar disorder. Qualitative data were assessed by the normalization process model (NPM). The results demonstrate feasibility of implementation with expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Herbert et al [ 97 ] UK NPT Enhanced recovery after surgery Process evaluation Qualitative Prospective Yes Yes N/A 64. Hoberg et al [ 98 ] USA NPM Group therapy model APA guideline [ 234 ] Feasibility study Qualitative Prospective Yes No No 65. Holtrop et al [ 99 ] USA NPT (collective action constructs) Care management for chronic disease in primary care Yes Process evaluation Qualitative Prospective Yes No Yes 66.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Herbert et al [ 97 ] UK NPT Enhanced recovery after surgery Process evaluation Qualitative Prospective Yes Yes N/A 64. Hoberg et al [ 98 ] USA NPM Group therapy model APA guideline [ 234 ] Feasibility study Qualitative Prospective Yes No No 65. Holtrop et al [ 99 ] USA NPT (collective action constructs) Care management for chronic disease in primary care Yes Process evaluation Qualitative Prospective Yes No Yes 66.…”
Section: Resultsmentioning
confidence: 99%
“…They used NPT in ‘identifying and describing the components and sub-components of the intervention’ to understand ‘the nuances associated with collective implementation’. The next most numerous group of studies focused on the implementation of diagnostic and therapeutic interventions ( n = 28, 25.9% [ 19 , 24 26 , 28 31 , 36 , 37 , 47 , 48 , 55 57 , 67 , 69 , 78 , 80 , 90 , 95 , 97 , 98 , 103 , 104 , 111 , 117 , 123 , 126 , 137 , 142 , 143 ]). For example, in the USA, Hoberg et al [ 98 ] examined the implementation of a new form of group therapy for people with mental health problems, while Leon et al [ 48 ] showed how provider initiated testing and counselling for HIV was successfully normalised in a South African setting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two small studies failed to demonstrate specific benefits of IPSRT compared to control conditions 99, 100. Other open studies have shown some pre‐post benefits in very small samples 101, 102, 103. Again, since many psychosocial treatments for bipolar disorder share common core elements that may be psychoeducational, it is possible that the relapse prevention aspects of psychoeducation may also result from IPSRT interventions, mediated by the same therapeutic processes 104…”
Section: Foundations Of Managementmentioning
confidence: 99%
“…KİSRT'nin bireysel terapilerin yanı sıra bipolar bozuklukta grup terapisinde de deneyimli klinisyenlerce ve program koordinasyonu sağlanması ile kullanılabileceği bildirilmiştir. [35] Bipolar bozuklukta grup terapisinde yapılan KİSRT uygulamasında bir yıllık süreçte depresif belirtilerde ve hastaneye yatış oranlarında azalma olduğu bildirilmiştir. [36] Bipolar bozukluk tanısı olan 12 ergende KİSRT uygulanan bir açık çalışmada ise hastaların seanslara düzenli katılma oranı %97 olarak bulunmuş, 20 haftalık terapi sonunda manik, depresif ve genel psikiyatrik belirtilerde anlamlı düzelme izlenmiştir.…”
Section: Bipolar Bozuklukta Ki̇srt Etkinliğiunclassified